Worries and Experiences of Male Student Nurses during Their Public Health Internship: Şanlıurfa Example - Adskhan Öztürk (International Journal of Science and Society, 2020)
The aim of the study is to describe the concerns and experiences of male student nurses who will go on a public health internship for the first time. This is a descriptive study conducted with 27 male nurses who took a Public Health internship at Harran University School of Health. Data were collected through a semi-structured interview form. All of the male students went to home visits with their girlfriends. They stated that they could not communicate directly during home visits and the internship was not very efficient in this state. Male students faced resistance in public health practices, so it was determined that they were not beneficial to both society and themselves, learning decreased and change was slow.